An Economic Analysis of Reconstruction Projects at Public Hospitals A Study within the Swedish Regional Healthcare Sector - Lund, Max; Svedberg, Carl (My University, 2024)
A majority of the hospitals in Sweden were built during the 1960s and 1970s, and their state today entails a need for investments. Current financial deficits across regions, future healthcare requirements, and an increasing dependency ratio together with undeveloped capital budgeting within the hospital sector, call for an economic analysis of these reconstruction projects. Therefore, the purpose of the thesis is to identify and analyze key factors to achieve economically profitable reconstruction projects at public hospitals. This is accomplished through two research studies, where the first quantitatively investigates a single case of the Hospital of Kungälv, and the second qualitatively investigates a multiple case study across Swedish regions with 21 interviews. The first study resulted in a business case model to evaluate how a hospital reconstruction project can become economically profitable. To achieve an economic break-even point productivity must increase and a sensitivity analysis shows that the discount rate, the facility investment cost, increased rent, the facility economic lifetime, and the compensation per surgery and patient are important financial posts to consider. The second research study resulted in a framework including key factors for management to consider when aiming to achieve profitable reconstruction projects in the healthcare sector. These key factors are a comprehensive vision, early planning, communication and cooperation, focus on efficiency, management, efficient facility utilization, and cost consciousness. The presented findings contribute to this research area in the Swedish setting and can be a foundation for future research within the field.
Keywords: Business Case; Economic Profitability; Hospital Management; Key Factors; Public Sector; Reconstruction Projects